2009
DOI: 10.1093/jaoac/92.3.745
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Planar Chromatographic Analysis of 25 Water-Soluble Dyes Used as Food Additives

Abstract: A rapid planar chromatographic method for identification and quantification of 25 water-soluble dyes in food was developed. In a horizontal developing chamber, the chromatographic separation on silica gel 60F254 high-performance thin-layer chromatography plates took 12 min for 40 runs in parallel, using 8 mL ethyl acetatemethanolwateracetic acid (65 + 23 + 11 + 1, v/v/v/v) mobile phase up to a migration distance of 50 mm. However, the total analysis time, inclusive of application and evaluation, took 60 min fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…In the positive ion mode, the mass signals were marginal. For the dyes investigated, the desodiated molecule of E 103 at m/z 293.0 [M−Na] − , the twofold deprotonated molecule of E 105 at m/z 177.6 [M−2H] 2− and for the other dyes (E 111, E 127 and E 133) the twofold desodiated molecules [M−2Na] 2− were the dominant and characteristic base peaks ( Table 2 ), as already reported in [ 17 ] using HPTLC plates silica gel 60. Other minor signals in the mass spectra of the electrospun layers originated from the plate background.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…In the positive ion mode, the mass signals were marginal. For the dyes investigated, the desodiated molecule of E 103 at m/z 293.0 [M−Na] − , the twofold deprotonated molecule of E 105 at m/z 177.6 [M−2H] 2− and for the other dyes (E 111, E 127 and E 133) the twofold desodiated molecules [M−2Na] 2− were the dominant and characteristic base peaks ( Table 2 ), as already reported in [ 17 ] using HPTLC plates silica gel 60. Other minor signals in the mass spectra of the electrospun layers originated from the plate background.…”
Section: Resultssupporting
confidence: 76%
“…On the manufactured electrospun PAN nanofiber phase, the linear calibrations of water-soluble food dyes obtained by videoevaluation resulted in precisions of the linear calibration functions of 3.1–9.1% (mean % RSD 5.7%) for peak heights and 2.4–9.3% (mean % RSD 5.5%) for peak areas ( Table 1 ). Hence, the quality (characterization by SEM), good efficiency (separation time and resolution), and performance (precisions and linear calibrations) of the electrospun PAN nanofiber phase for quantitative studies on such upcoming layer materials was successfully demonstrated, if compared to a powerful HPTLC method [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…A number of different methods have been published for the analysis of Brilliant Black BN in foods, mostly based on clean-up by adsorption onto polyamide (powder or a column) followed by chromatographic determination. High Performance Liquid Chromatography (HPLC) has been mostly employed with diode array detection (Kirschbaum et al, 2006;Yoshioka and Ichihashi, 2008), but other approaches such as High Performance Thin Layer Chromatography (HPTLC) (Morlock and Oellig, 2009) and Capillary Electrophoresis (CE) have also been advocated (Frazier et al, 2000). Although diode array detection does provide some level of confirmation from scanned spectra, the most unequivocal identification of Brilliant Black BN in foods was conducted by eluting HPTLC zones for subsequent mass spectral confirmation (Morlock and Oellig, 2009).…”
Section: Methods Of Analysis In Foodmentioning
confidence: 99%
“…A number of different methods have been published for the analysis of Amaranth in various foods including direct analysis of beverages (Vachirapatama et al, 2008), including extraction into dimethyl sulfoxide (DMSO) (Ma et al, 2006) or clean-up by adsorption onto polyamide powder or polyamide columns (Kirschbaum et al, 2006;Morlock and Oellig, 2009) followed in each case by chromatographic determination. High Performance Liquid Chromatography (HPLC) with diode array detection has been mostly employed (Kirschbaum et al, 2006;Yoshioka and Ichihasi, 2008), although other approaches such as High Performance Thin Layer Chromatography (HPTLC) have also been used (Morlock and Oellig, 2009). Although diode array detection does provide some level of confirmation from scanned spectra, the most unequivocal identification of Amaranth in foods was conducted with electrospray Liquid Chromatography-Mass Spectrometry (LC-MS) (negative ionisation) using selected ion monitoring of m/z 537 (Ma et al, 2006).…”
Section: Methods Of Analysis In Foodmentioning
confidence: 99%
“…Although diode array detection does provide some level of confirmation from scanned spectra, the most unequivocal identification of Amaranth in foods was conducted with electrospray Liquid Chromatography-Mass Spectrometry (LC-MS) (negative ionisation) using selected ion monitoring of m/z 537 (Ma et al, 2006). Methods have been applied to soft drinks and confectionery (Yoshioka and Ichihasi, 2008), soft drinks and bakery inks (Morlock and Oellig, 2009) and fish roe and caviar (Kirschbaum et al, 2006) (with recoveries for example of 91% from soft drinks and 93% from confectionery, CV = 2.1-5.4%). It can be concluded that methods of analysis for Amaranth in selected foods appear to be reliable, have received some validation and would be appropriate for use for survey or enforcement purposes.…”
Section: Methods Of Analysis In Foodmentioning
confidence: 99%